HEMOLYTIC UREMIC SYNDROME - Ngurah Wisesa, Ida Bagus; Loekman, Jodi S (journal of internal medicine, 2009)
Hemolytic uremic syndrome (HUS) is caused primarily by Shiga toxin–producing Escherichia coli O157:H7. Hemolyticuremic syndrome can occur in adults, and the most common cause of acute renal failure in children. Characteristic features of thesyndrome are microangiopathic anemia, thrombotic thrombocytopenia, and renal failure. Although the presentation of this syndromeis diverse, the classic prodromal illness is bloody diarrhea. Children with HUS generally present with gastroenteritiscomplaints (e.g., abdominal pain or tenderness, nausea or vomiting, fever, anemia); affected adults may be asymptomatic. Complicationsfrom HUS can include intussusception, chronic renal failure, and seizures in severe cases. Because an incubation periodof approximately one week occurs between the start of diarrhea and the onset of HUS, physicians should maintain a high index ofsuspicion; early laboratory testing is important to diagnose and manage this syndrome. Obtaining a complete blood count andstool culture and performing Shiga toxin testing are the first of a series of tests that may help diagnose of HUS.